ANALISA PENGARUH FAKTOR EKSPOSI TERHADAP ENTRANCE SURFACE AIR KERMA (ESAK) - Muahamad Irsal; Eko Hidayanto; Zaenal Arifin (Youngster Physics Journal, 2014)
The research has been analyzed of the effect of exposure factors at the entrance surface air kerma (ESAK) of the thorax radiographs. This research uses anthropomorphic phantom, multipurpose detectors, FFD 100 cm, with radiation field 25 cm × 25 cm. irradiation conditions is given by the variation of expose factors using tube voltage 50-100 kV and tube current-time 2-20 mAs. The results of research showed that the effect of the tube voltages to the entrance surface air kerma experience is increase a specific approximated by an polynomial equation with a correlation coefficient value R2 = 1 and the variation of the tube current-time increased linearly approximated by a approach linear equation R2 = 1, uses of tube current time under 4 mAs with resulted lower the entrance surface air kerma based on IAEA Safety Series No. 115 (1996) is 0.4 mGy at examination of thorax radiographic, and conducted a calculation uncertainly  value of every expose factors using variations of tube voltage and tube current-time based on scenarios three of IAEA Technical Report Series No. 457(2007).Keywords: entrance surface air kerma, thorax radiography, the tube voltage, tube current-time, phantom anthoropomorphic.